SUBSTITUTION OF COUPLE Sn(IV)/Zn(II) FOR In(III) IN THE FLUORITE-LIKE TRANSPARENT CONDUCTORS: In₅₋₂ₓSn₁₊ₓSbZnₓO₁₂ - BIZO, L.; MAGYARI, K. (Studia Universitatis Babeș-Bolyai Physica, 2015)
Three new compositions (x = 0.1, x = 0.2 and x = 0.3) belonging to In5-2xSn1+xSbZnxO12 system, have been successfully synthesized by substitution of pair Sn(IV)/Zn(II) for In(III). The compositions were studied from point of view of structural, optical and electrical properties. Structure calculations shows an ordered cationic distribution over the octahedral and highly distorted sevenfold coordinated site. For In4.4Sn1.3SbZn0.3O12 composition a small amount of unreacted SnO2 was identified, which decreases from 5.76 wt % to 3.17 wt %, by increasing preparation temperature from 1300 °C to 1350 °C. The electrical conductivity of the x = 0.1 composition was enhanced by approximately one order of magnitude with respect to In4Sn3O12.